Comparison of single high-dose streptozotocin with partial pancreatectomy combined with low-dose streptozotocin for diabetes induction in rhesus monkeys - Jin, X.; Zeng, L.; He, S.; Chen, Younan; Tian, B.; Mai, G.; Yang, G.; Wei, L.; Zhang, Y.; Li, H.; Wang, L.; Qiao, C.; et al. (SAGE Publications Inc., 2010)
Monkeys with insulin-dependent diabetes are important experimental models for islet xenotransplantation. However, with regard to diabetes induction, total pancreatectomy is a difficult operation with a high complication rate, while streptozotocin (STZ) administration may cause serious toxic effects and individual difference in metabolism. We compared two strategies involving pancreatectomy and STZ to successfully and safely induce diabetes in rhesus monkeys. Thirteen rhesus monkeys were divided into two groups: single high-dose STZ administration (80, 100 and 120 mg/kg, n = 3 for each dose) (group 1) and partial pancreatectomy (70-75%) combined with low-dose STZ (15 mg/kg, n = 4) (group 2). Induction of diabetes was evaluated by blood glucose, insulin, C-peptide, intravenous glucose tolerance test (IVGTT) and arginine stimulation test (AST). Detection of hematological and serum biochemical parameters and biopsies of pancreas, liver and kidney were periodically performed. In our study, animals in both groups developed diabetes. Serum C-peptide levels in groups 1 and 2 decreased to 0.08±0.07 and 0.35±0.06 nmol/L, respectively. IVGTT and AST indicated severely impaired glucose tolerance. Immunohistochemistry demonstrated that rare insulin-positive cells remained in the pancreas. In terms of STZ toxicity, four monkeys died 8-14 days after STZ administration (3 with 120 mg/kg STZ and 1 with 100 mg/ kg STZ). Group 1 animals developed liver and kidney injury evidenced by increased alanine aminotransferase, aspartate aminotransferase, total cholesterol, LDL, triglyceride and blood urea nitrogen for one month, and histological abnormality including hepatic steatosis, renal glomerulus and tubular injury. Nevertheless, moderate histological injuries were seen in animals with 80 mg/kg STZ, with subsequent recovery. In contrast, group 2 animals displayed normal biochemical parameters and histology, with generally less risk of postoperative complications. We conclude that injection of 80 mg/kg STZ could induce diabetes with moderate injuries. Partial pancreatectomy with low-dose STZ is a safer and more reproducible method for inducing diabetes in rhesus monkeys. Copyright © 2010 by the Society for Experimental Biology and Medicine.